(1‐Butyl‐4‐methyl‐pyridinium)[Cu(SCN)2]: A Coordination Polymer and Ionic Liquid. Issue 18 (18th March 2014) - Eike T. Spielberg; Edengeiser, Eugen; Mallick, Bert; Havenith, Martina; Mudring, Anja‐Verena
Abstract The compound (C4C1py)[Cu(SCN)2], (C4C1py=1‐Butyl‐4‐methyl‐pyridinium), which can be obtained from CuSCN and the ionic liquid (C4C1py)(SCN), turns out to be a new organic–inorganic hybrid material as it qualifies both, as a coordination polymer and an ionic liquid. It features linked [Cu(SCN)2]− units, in which the thiocyanates bridge the copper ions in a μ1, 3‐fashion. The resulting one‐dimensional chains run along the a axis, separated by the C4C1py counterions. Powder X‐ray diffraction not only confirms the single‐crystal X‐ray structure solution but proves the reformation of the coordination polymer from an isotropic melt. However, the materials shows a complex thermal behavior often encountered for ionic liquids such as a strong tendency to form a supercooled melt. At a relatively high cooling rate, glass formation is observed. When heating this melt in differential scanning calorimetry (DSC) and temperature‐dependent polarizing optical microscopy (POM), investigations reveal the existence of a less thermodynamically stable crystalline polymorph. Raman measurements conducted at 10 and 100 °C point towards the formation of polyanionic chain fragments in the melt. Solid‐state UV/Vis spectroscopy shows a broad absorption band around 18 870 cm−1 (530 nm) and another strong one below 20 000 cm−1 (<500 nm). The latter is attributed to the d(CuI)→π*(SCN)‐MLCT (metal‐to‐ligand charge transfer) transition within the coordination polymer yielding an energy gap of 2.4 eV. At room temperature and upon irradiation with UV light, the material shows a weak fluorescence band at 15 870 cm−1 (630 nm) with a quantum efficiency of 0.90(2) % and a lifetime of 131(2) ns. Upon lowering the temperature, the luminescence intensity strongly increases. Simultaneously, the band around 450 nm in the excitation spectrum decreases.